A triterpene and four sesquiterpenes from the Vietnamese sea hare Aplysia dactylomela - Pham, Thanh Binh; Duong, Thu Trang; Vu, Thanh Trung; Kieu, Thi Phuong Linh; Le, Ba Vinh; Nguyen, Phuong Thao; Nguyen, Chi Mai; Tran, My Linh; Nguyen, Van Thanh (Vietnam Journal of Marine Science and Technology, 2026)
Five compounds, including thyrsiferol (1), 11-hydroxy-8-oxo-β-cyperon (2), (+)-elatol (3), [3(15)E,4Z,6S,9S,10R]-10,15-dibromochamigra-3(15),4,7(14)-trien-9-ol (4), and pacifidiene (5) were isolated from the methanol extract of the sea hare Aplysia dactylomela, collected at Quang Ngai province, Vietnam. Their structures were elucidated from HR-ESI-MS and NMR spectral data. Compound 2 was obtained for the first time from A. dactylomela, and its complete NMR spectral data were reported here. All isolated compounds were evaluated for cytotoxic activity against three human cancer cell lines (A549, MCF-7, and HepG2). Among them, compound 3 exhibited significant cytotoxicity against all tested cell lines, with IC50 values ranging from 5.07 ± 0.96 to 6.55 ± 0.44 μM.